2019
DOI: 10.1002/jcb.28346
|View full text |Cite
|
Sign up to set email alerts
|

ZCCHC9 promotes proliferation and invasion of lung cancer through regulating the JNK pathway

Abstract: ZCCHC9 is a type of CCHC type zinc-finger containing protein which was found to be expressed in some tissues including brain and testicles in mice. Expression and function of ZCCHC9 in human tissues including cancer was largely unknown. In this study, we investigated the expression and function of ZCCHC9 in human non-small cell lung cancer (NSCLC) and the related molecular mechanism. Immunochemistrical standing showed that ZCCHC9 was mainly located in the nucleus in bronchial epithelial cells and epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…59 It has been widely reported that many key genes affecting lung cancer function through these two pathways. 60,61 In this study, changes in HBA and HBB affected the synthesis of p38 and JNK proteins, suggesting that they may also have a similar mechanism of action. which is a new starting point on searching for biomarkers.…”
Section: Discussionmentioning
confidence: 50%
“…59 It has been widely reported that many key genes affecting lung cancer function through these two pathways. 60,61 In this study, changes in HBA and HBB affected the synthesis of p38 and JNK proteins, suggesting that they may also have a similar mechanism of action. which is a new starting point on searching for biomarkers.…”
Section: Discussionmentioning
confidence: 50%
“…It also up-regulates the JNK pathway activity in the MAPK pathway subfamily in lung cancer cells such as A549 and NCI-H1299 to promote the proliferation and invasion of cancer cells. 24,30 This indicates that ZCCHC9 has a potential role in the MAPK signaling cascade. Oxidative stress, that is, reactive oxygen species that mediate a series of biochemical reactions in cells through MAPK signaling pathways, is related to AMI.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that CCHC‐type zinc finger proteins play biological functions in tumour tissues via regulating the MAPK signalling pathway 2‐5 composed of ERK1/2, P38, ERK5 and JNK 18 . While ZCCHC14 is a protein containing multiple zinc finger motifs, there are no studies on its possible involvement in the signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Transwell assays were performed as described 11 . Cell suspensions (100 µl containing 1 × 10 4 cells) were placed in the upper chamber and were then incubated for an additional 24 hours. Cells appearing on the lower surface of the filter were stained with crystal violet and five random fields were counted using a high‐magnification microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation